2023
DOI: 10.1111/tmi.13895
|View full text |Cite
|
Sign up to set email alerts
|

Interest of seroprevalence surveys for the epidemiological surveillance of the SARS‐CoV‐2 pandemic in African populations: Insights from the ARIACOV project in Benin

Abstract: Background Many SARS‐CoV‐2 seroprevalence surveys since the end of 2020 have disqualified the first misconception that Africa had been spared by the pandemic. Through the analysis of three SARS‐CoV‐2 seroprevalence surveys carried out in Benin as part of the ARIACOV project, we argue that the integration of epidemiological serosurveillance of the SARS‐CoV‐2 infection in the national surveillance packages would be of great use to refine the understanding of the COVID‐19 pandemic in Africa. Methods We carried ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In Benin as of April 2024, 28,036 cases of COVID-19 had been reported [ 1 ]. None of the study participants had been diagnosed with COVID-19 during their pregnancy, and although there is no data on prior COVID-19 diagnosis, it is most likely that COVID-19 cases may have not been entirely captured by routine surveillance systems, as 76.4% of the unvaccinated study participants presented antibodies, which is also in accordance with the seroprevalence studies performed in the general population in Cotonou and Natitingou [ 2 ]. In the same line, a meta-analysis reporting on SARS-CoV-2 global seroprevalence has found that the ratio of seroprevalence to cumulative incidence of confirmed cases reported by the WHO ranged from 82.2:1 in July-September 2020 to 176.7:1 in July-September 2021 in the WHO African region, in comparison to global ratios ranging from 51.3:1 to 10.5:1.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In Benin as of April 2024, 28,036 cases of COVID-19 had been reported [ 1 ]. None of the study participants had been diagnosed with COVID-19 during their pregnancy, and although there is no data on prior COVID-19 diagnosis, it is most likely that COVID-19 cases may have not been entirely captured by routine surveillance systems, as 76.4% of the unvaccinated study participants presented antibodies, which is also in accordance with the seroprevalence studies performed in the general population in Cotonou and Natitingou [ 2 ]. In the same line, a meta-analysis reporting on SARS-CoV-2 global seroprevalence has found that the ratio of seroprevalence to cumulative incidence of confirmed cases reported by the WHO ranged from 82.2:1 in July-September 2020 to 176.7:1 in July-September 2021 in the WHO African region, in comparison to global ratios ranging from 51.3:1 to 10.5:1.…”
Section: Discussionsupporting
confidence: 78%
“…The underreporting of COVID-19 cases in Benin has already been pointed by SARS-CoV-2 seroprevalence surveys performed at the community level in the country, which found that SARS-CoV-2 seroprevalence was over 30% from March to August 2021 [ 2 ]. In addition, our results, obtained one year afterwards, suggest that SARS-CoV-2 seroprevalence has raised greatly from mid-2021 to mid-2022.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations